Morphological Characteristics of Adaptation of the Lungs in the Ground Spinal - K.A. Saparov ,; Z.B. Yessimsiitova ,; B.A. Abdullayeva ,; S.A. Mankibaeva ,; B.M. Tynybekov ,; G.K. Atanbayeva ,; S.N. Abdreshov Kazakh, (Journal of Pharmacy and Nutrition Sciences, 2019)
This article discusses the morphological changes in the structures of the lungs when adapting to some extreme factors and environmental conditions. One of the most pressing problems of biology is the elucidation of the mechanisms of adaptation of the human body and animals to changing environmental conditions [1-7]. This problem can be viewed in two aspects: firstly, in terms of the emergence of adaptive rearrangements in the body when exposed to environmental factors as a manifestation of the body's plasticity in ontogenesis, secondly, in terms of the emergence of adaptation, as genetically and phenotypically fixed adaptation of living organisms to the conditions environment, which arose in the course of evolution [8-13]. The key point here is the identification and comparison of subtle mechanisms of similar (to the same environmental factor) adaptation that arise in ontogenesis and formed in phylogenesis [14-21].